Motivasi dan Sarana Prasarana Latihan Atlet Provinsi Bengkulu Menuju PON XX Papua - Desti Dui Nilasari; Syafrial Syafrial; Bogy Restu Illahi (Universitas Bengkulu, 2020)
The purpose of this research was to find out how to Motivate and Training Facilities of Bengkulu Province Athletes for PON XX Papua. This type of research is a qualitative descriptive study. The subjects in this study was all Bengkulu Province sports branches for PON XX Papua with 83 athletes and 16 trainers. The instruments and data collection techniques that i used in this study was questionnaire and member check. The data analysis technique that i used was descriptive analysis with a percentage. The result of this research declared that athlete training motivation is 85,40 % with the very well category and facilties-infrastructure training atlhete 1 branch of rock climbing was 6,25% with the very well category 9 branch of volley ball, badminton, tennis, silat, boxing, wrestling, karate, diving PABBSI is 56,25% with good category and 6 branch football, muay thai, kempo, Athletic, swimming, and biliard is 37,5 % with the medium category based on result of this research can be concluded that motivation atlhete with very well category and facilities-infrasturcture with good category.